The Expansion of Information and Communications Technologies: Theoretical Approaches and Security Considerations of Iran - Morteza Nourmohammadi; Roohollah Talebi Arani (Faṣlnāmah-i Pizhūhish/hā-yi Rāhburdī-i Siyāsat, 2016)
Technology always has played an increasingly vital role in shaping human life. In terms of International Relations, the existence of nuclear weapons technology affected politics during Cold War era, but, nowadays, in the Age of Information, Information and communications technology play an increasingly vital role in international system, international security, war and conflicts. Thus, drawing a content analysis on significant theoretical classic texts in international relations, the article seeks to explain whether and to what extent three grand theoretical approaches to international relations, realism, liberalism and constructivism, have theoretically paid attention to a role played by the expansion of Information and communications technology in international arena. The article concluded that international relations theories would have experience a conceptual development. The reflexivist criticism of the dominant theoretical approaches of international relations grow more severe, and theories such as constructivism would be more significant than ever.